Edge tracing technique to study post‐necking behavior and failure in Al alloys and anisotropic plasticity in line pipe steels. Issue 9 (7th June 2022) - Shokeir, Zacharie; Besson, Jacques; Belhadj, Chiraz; Petit, Tom; Madi, Yazid
Abstract: The recently developed edge tracing (ET) method allows to estimate the radial deformation in axisymmetric tensile specimens via analysis of digital images recorded during the experiments. Images are processed to detect the sample's contours and therefore estimate the minimal cross‐section diameter. This technique was mainly developed to characterize the plastic behavior well beyond the necking strain. The aim of this work is to apply the ET method to two novel case studies. Firstly, the post‐necking behavior and failure of a low ductility Al alloy are investigated. Low ductility alloys tend to fail brutally after reaching the maximum load. The major result is the capture of the sharp load drop which allowed to calibrate parameters of a GTN damage model. Secondly, the anisotropic elastic–plastic behavior of a "vintage" line pipe steel is characterized by a direct measurement of the Lankford coefficient. Assembled experimental data allowed to model the anisotropic plasticity beyond necking in different loading directions. HIGHLIGHTS: Radial deformation in tensile specimens before and beyond necking can be accurately estimated via images recorded during testing: Edge Tracing Method (ETM). ETM helps in assessing failure and calibrating GTN damage parameters. ETM method allows evaluating continuously the plastic anisotropy in line pipe steels which is essential for fracture analysis in anisotropic materials. Isotropic and anisotropic elastic–plasitc hardening laws can be fit without the Bridgman correction thanks to the ET technique.